Study of termites infestation in buildings / Muhammad Mahroz Mat Johari - Mat Johari, Muhammad Mahroz (2006)
Termites are the most destructive wood pests. They cause damage by feeding on the wooden structure of a home such as beams, door frames, wooden paneling, floor parquet, cupboards, even books or newspaper. Thus, it is important to prevent termites from entering your home by protecting the wooden areas and its surroundings with a reliable and effective termiticide. Besides that termites become economic pests when their appetite for wood and wood products extends to human homes, building materials, forests, and other commercial products. Basically there are various types of termites in the world. However, types of termites are found in Malaysia, normally from subterranean termites like as captotermes species. In Malaysia, most problems with termites only surfaced a while after the property is constructed. The common method used by developers to assess soil condition was by looking for mounds but this was ineffective as most of the destructive termites did not build any mounds. In Malaysia, have a few methods prevention of termites infestation which are applied.